Perceived Quality Mediates Lifestyle and Product Reviews Effects on Elformula Purchase Intention - Enriya Anjani; Ali Ali (Jurnal Manajemen Sains dan Organisasi, 2026)
Objective – This study aims to analyze the role pf perceived quality as a mediating variable in the relationship between lifestyle and product review on purchase intention of Elformula skincare products. Design/Methodology/Approach – This study applied a quantitative method and data were collected through online questionnaires distributed to consumers who are familiar with and interested in Elformula. A total of 171 responses were obtained using purposive sampling. The data were analyzed using PLS-SEM with SmartPLS 3.0 to examine both direct and indirect relationships among lifestyle, product review, perceived quality, and purchase intention. Findings – The results show that lifestyle and product reviews do not have significant direct effect on purchase intention. However, both variables significantly and positively influence perceived quality. Perceived quality has a strong positive effect on purchase intention and fully mediates the relationship between lifestyle and purchase intention as well as between product reviews and purchase intention. Conclusion and Implications – This study contributes to consumer literature by highlighting perceived quality as a key mediating construct in the skincare industry context. It extends the Theory of Planned Behavior by demonstrating that perceived quality functions as an attitudinal mechanism linking lifestyle and product reviews to purchase intention, particularly for experience-based product.